Freshwater fish distribution [ - Berra, Tim M. , 1943- (University of Chicago Press, 2007)
With more than 29,000 species, fishes are the most diverse group of vertebrates on the planet. Of that number, more than 12,000 species are found in freshwater ecosystems, which occupy less than 1 percent of the Earths surface and contain only 2.4 percent of plant and animal species. But, on a hectare-for-hectare basis, freshwater ecosystems are richer in species than more extensive terrestrial and marine habitats. Examination of the distribution patterns of fishes in these fresh waters reveals much about continental movements and climate changes and has long been critical to biogeographical.